Deep eutectic solvent in water pickering emulsions stabilised by cellulose nanofibrils. Issue 61 (7th October 2020) - Bryant, Saffron J.; da Silva, Marcelo A.; Hossain, Kazi M. Zakir; Calabrese, Vincenzo; Scott, Janet L.; Edler, Karen J.
Abstract : Deep eutectic solvent in water emulsions stabilised with bio-macromolecules were stable for more than 200 days. Abstract : Deep eutectic solvent (menthol : dodecanoic acid) in water (30 : 70) emulsions stabilised with partially oxidised cellulose nanoparticles remained stable for 200 days at room temperature. Deep eutectic-based emulsions offer potential for non-aqueous reaction systems, chemical extraction, and controlled release. Pickering emulsions using polysaccharides are less toxic and more stable than surfactant-stabilised emulsions.